Exploiting the gut microbiota to predict the origins and quality traits of cultured sea cucumbers. (16th March 2022) - Zhao, Zelong; Jiang, Jingwei; Zheng, Jie; Pan, Yongjia; Dong, Ying; Chen, Zhong; Gao, Shan; Xiao, Yao; Jiang, Pingzhe; Wang, Xuda; Zhang, Gaohua; Wang, Bai; et al.
Summary: Nowadays, the true economic and nutritional value of food is underpinned by both origin and quality traits, more often expressed as increased quality benefits derived from the origin source. Gut microbiota contribute to food metabolism and host health, therefore, it may be suitable as a qualifying indicator of origin and quality of economic species. Here, we investigated relationships between the gut microbiota of the sea cucumber ( Apostichopus japonicus ), a valuable aquaculture species in Asia, with their origins and quality metrics. Based on data from 287 intestinal samples, we generated the first biogeographical patterns for A . japonicus gut microbiota from origins across China. Importantly, A . japonicus origins were predicted using the random forest model that was constructed using 20 key gut bacterial genera, with 97.6% accuracy. Furthermore, quality traits such as saponin, fat and taurine were also successfully predicted by random forest models based on gut microbiota, with approximately 80% consistency between predicted and true values. We showed that substantial variations existed in the gut microbiota and quality variables in A . japonicus across different origins, and we also demonstrated the great potential of gut microbiota to track A . japonicus origins and predict their quality traits.